Non-equilibrium structural dynamics of supercoiled DNA plasmids exhibits asymmetrical relaxation. Issue 5 (21st February 2022) - Shaheen, Cynthia; Hastie, Cameron; Metera, Kimberly; Scott, Shane; Zhang, Zhi; Chen, Sitong; Gu, Gracia; Weber, Lisa; Munsky, Brian; Kouzine, Fedor; Levens, David; Benham, Craig; et al.
Abstract: Many cellular processes occur out of equilibrium. This includes site-specific unwinding in supercoiled DNA, which may play an important role in gene regulation. Here, we use the Convex Lens-induced Confinement (CLiC) single-molecule microscopy platform to study these processes with high-throughput and without artificial constraints on molecular structures or interactions. We use two model DNA plasmid systems, pFLIP-FUSE and pUC19, to study the dynamics of supercoiling-induced secondary structural transitions after perturbations away from equilibrium. We find that structural transitions can be slow, leading to long-lived structural states whose kinetics depend on the duration and direction of perturbation. Our findings highlight the importance of out-of-equilibrium studies when characterizing the complex structural dynamics of DNA and understanding the mechanisms of gene regulation.